The N-Terminal Extension of Cardiac Troponin T Stabilizes the Blocked State of Cardiac Thin Filament - Gollapudi, Sampath K. (The Biophysical Society, 2012)
Cardiac troponin T (cTnT) is a key component of contractile regulatory proteins. cTnT is characterized by a ∼32 amino acid N-terminal extension (NTE), the function of which remains unknown. To understand its function, we generated a transgenic (TG) mouse line that expressed a recombinant chimeric cTnT in which the NTE of mouse cTnT was removed by replacing its 1–73 residues with the corresponding 1–41 residues of mouse fast skeletal TnT. Detergent-skinned papillary muscle fibers from non-TG (NTG) and TG mouse hearts were used to measure tension, ATPase activity, Ca(2+) sensitivity (pCa(50)) of tension, rate of tension redevelopment, dynamic muscle fiber stiffness, and maximal fiber shortening velocity at sarcomere lengths (SLs) of 1.9 and 2.3 μm. Ca(2+) sensitivity increased significantly in TG fibers at both short SL (pCa(50) of 5.96 vs. 5.62 in NTG fibers) and long SL (pCa(50) of 6.10 vs. 5.76 in NTG fibers). Maximal cross-bridge turnover and detachment kinetics were unaltered in TG fibers. Our data suggest that the NTE constrains cardiac thin filament activation such that the transition of the thin filament from the blocked to the closed state becomes less responsive to Ca(2+). Our finding has implications regarding the effect of tissue- and disease-related changes in cTnT isoforms on cardiac muscle function.